EFISIENSI PEMASARAN PRODUK DUKU LAMPUNG MELALUI PENDEKATAN SERBA FUNGSI DI KABUPATEN LAMPUNG SELATAN - Ramadinata, Firham; Hasyim, Ali Ibrahim; Situmorang, Suriaty (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
The objectives of this research were to find out Lampung’s duku marketing efficiency that was viewed from functions served by each of marketing agencies in Katibung subdistrict of South Lampung district and producer share, marketing margin and margin profit ratio. This research was conducted in Katibung sub district as the production center and the biggest production site of Lampung duku in Lampung. The location was selected purposively. Data were collected from May to June 2013. Samples were taken by using marketing channel method. The samples were consisted of 50 farmers, 12 small collector traders, 5 big traders, and 5 groceries. Data were analyzed using descriptive qualitative method (with multifunction approach) and quantitative method (producer share, marketing margin and margin profit ratio). The results showed that Lampung duku marketing in Katibung sub district of South Lampung district was not efficient, because some marketing functions were not operated properly such as storing and funding functions and producer share < 50%, marketing margin was so high that over two times average of farmer selling price, and the margin profit ratio of each marketing agency showed various and uneven values. Keywords : duku, efficiency, Lampung, marketing, multifunction